Demonstration of Solitary Chemosensory Cells in the Nasopalatine and Vomeronasal Ducts of Rat by ?-gustducin and GAP-43 Immunohistochemistry. - Ashraf A. El Sharaby; Ahmed G. Nomir; Ahmed K. Elgarhy (Academia Anatomica International, 2017)
In the present study, we used immunohistochemistry for ? - gustducin and Growth Associated Protein-43 (GAP-43) to examine the spatial distribution of the solitary chemosensory cells primarily in the nasopalatine ducts of rat at the time of weaning, which is lack in the literature. Methods: We found abundant solitary cells labeled with ?- gustducin in the nasopalatine duct and vomeronasal organ of rats. In the nasopalatine duct, these cells were more frequent in the medial wall epithelium; meanwhile appreciable number of ?-gustducin labeled cells were localized only in the neuroepithelium portion of the vomeronasal organ. We found the number of these cells increased toward the entries of the nasopalatine and vomeronasal ducts into the nasal cavity. We also found GAP-43 heavily expressed in the core of nasopalatine duct, close to the basement membrane and around the blood vessels and cavernous spaces of the vomeronasal organ. Results: GAP-43 labeled axons apposed the solitary chemosensory cells closely, either coursing along or wrapping the solitary chemosensory cells. Individual cells were apposed by one or a few intraepithelial nerve fibers and a single fiber sometimes contacted a few solitary chemosensory cells. Intraepithelial GAP-43 labeled fibers were more frequent toward the nasal cavity and the entry of nasopalatine and vomeronasal ducts in close association with the solitary chemosensory cells. Conclusion: We conclude that ? -gustducin-expressing cells alongside the GAP-43 intraepithelial nerves in the nasopalatine and vomeronasal ducts suggests that they share the same transduction mechanisms.